WORKSHOP ON STRENGTHENING MERDEKA CURRICULUM INSTRUCTIONAL MODULES AT SMA NEGERI 1 SAJINGAN - Ramadhan, Iwan; Imran, Imran; Prancisca, Stella; Astari, Zuri; Zatalini, Adhalia (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2024)
The Workshop on Strengthening Merdeka Curriculum Instructional Modules at SMA Negeri 1 Sajingan aims to enhance teachers' ability to develop instructional modules in line with the principles of the Merdeka Curriculum. This workshop is expected to improve the quality of teaching, strengthen teachers' competencies, and support educational development at SMA Negeri 1 Sajingan. Located in the Sajingan Besar district of Sambas, West Kalimantan, SMA Negeri 1 Sajingan is uniquely positioned near the Indonesia-Malaysia border. Through this workshop, the PKM team intends to provide valuable experience, share knowledge, and strengthen teachers' understanding of the Merdeka Curriculum instructional modules. The workshop is conducted using both individual and classical approaches. The classical approach is used for delivering theoretical content on instructional modules, while the individual approach is applied during hands-on module creation exercises. Preparation and authorization for this workshop took place in April 2024 at SMA Negeri 1 Sajingan, with the participants being the school's teachers. In the context of the Merdeka Curriculum, developing high-quality instructional modules is crucial for enhancing teacher professionalism, improving teaching skills, and boosting the overall quality of education. Well-designed instructional modules can aid teachers in creating lessons that meet students' needs and adhere to the Merdeka Curriculum principles. Therefore, this workshop is expected to positively contribute to improving educational quality at SMA Negeri 1 Sajingan and support the effective implementation of the Merdeka Curriculum.